1980
DOI: 10.1130/mem153-p427
|View full text |Cite
|
Sign up to set email alerts
|

Bitterroot dome-Sapphire tectonic block, an example of a plutonic-core gneiss-dome complex with its detached suprastructure

Abstract: The Bitterroot dome-Sapphire tectonic block appears to be a well-developed example of a plutoniccore gneiss-dome complex or infrastructure separated from the adjacent suprastructure by a gently dipping zone of mylonitic shearing or an "Abscherungszone." The suprastructural Sapphire block, on the order of 15 km thick, 100 km long, and 70 km wide, apparently moved eastward about 60 km, bulldozing rocks of the eastern Flint Creek Range ahead of it. Movement of the block must have occurred about 75 or 80 m.y. ago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
(10 reference statements)
0
36
0
Order By: Relevance
“…The amount of tectonic shortening that accompanied emplacement of the Sapphire thrust plate may be much greater than earlier estimates by Hyndman (1980) and Wallace (in Ruppel and others, 1981), because these interpretations did not account for large amounts of shortening among stacked thrust sheets. Hyndman's hypothesis proposed that shortening occurred along the decollement that bounded the "Sapphire tectonic block" ~nd _that the "tectonic block" was shortened internally by hstnc thrusts of relatively small displacement that joined the decollemellt at depth (Hyndman, 1980, fig.…”
Section: Implications Of the Style Of Deformation And Timing Of Plutomentioning
confidence: 70%
See 4 more Smart Citations
“…The amount of tectonic shortening that accompanied emplacement of the Sapphire thrust plate may be much greater than earlier estimates by Hyndman (1980) and Wallace (in Ruppel and others, 1981), because these interpretations did not account for large amounts of shortening among stacked thrust sheets. Hyndman's hypothesis proposed that shortening occurred along the decollement that bounded the "Sapphire tectonic block" ~nd _that the "tectonic block" was shortened internally by hstnc thrusts of relatively small displacement that joined the decollemellt at depth (Hyndman, 1980, fig.…”
Section: Implications Of the Style Of Deformation And Timing Of Plutomentioning
confidence: 70%
“…Alternatively, Desmarais (1983) suggested that the southern boundary of the Sapphire plate may be just south of the mapped area, and that the boundary may be defined by a northwesttrending zone of ductile shear, which is expressed as a prominent foliation in syntectonic Cretaceous plutons and in metamorphic pendants of Middle Proterozoic rocks. The two-fold subdivision of the Sapphire thrust plate used in this report identifies a terrane of stacked thrust sheets and a frontal zone of imbricate thrust faults (Lidke, 1985;Lidke and others, 1987); these terranes cross boundaries of earlier lithotectonic subdivisions proposed by Hyndman (1980) and by Wallace (in Ruppel and others, 1981). Hyndman (1980) defined two lithotectonic elements in the area of the Sapphire thrust plate as (1) a western part, the "Sapphire tectonic block," which consisted of allochthonous Middle Proterozoic rocks, and (2) an eastern part, the "bulldozed" terrane, which was composed mostly of parautochthonous Paleozoic and Mesozoic rocks.…”
Section: Regional Tectonic Settingmentioning
confidence: 81%
See 3 more Smart Citations